PELAKSANAAN MANAGEMENT PROCEDURE PENGELOLAAN SUMBERDAYA IKAN BERKELANJUTAN DI INDONESIA - Chomariyah Chomariyah (Legality : Jurnal Ilmiah Hukum, 2017)
At the eighteenth annual meeting of the CCSBT agreed on the use of Management Procedure (MP) as a guide to total allowable catches globally against Southern Bluefin Tuna. It aims to ensure that the biomass of fish stocks can reach the target redevelopment of up to 20%. CCSBT set the allowable catch based on the results of the MP. MP aims to maintain the stability of the fishing industry reduces the possibility of the number of catches in the future to decrease. Three-year period total allowable catches globally is; 2014 is 12 449 tons, year 2015-2017 is 14 647 tons and 17 647 tons Year 2018-2020 be included ndonesia. Implementation Management Procedure by Indonesia is a resource management strategy that allows the fish formally to ensure that the fish resources can be utilized in a sustainable manner.